The Bacteriophage vB_CbrM_HP1 Protects Crucian Carp Against Citrobacter braakii Infection - Huang, Chunzheng; Feng, Chao; Liu, Xiao; Zhao, Rihong; Wang, Zijing; Xi, Hengyu; Ou, Hongda; Han, Wenyu; Guo, Zhimin; Gu, Jingmin; Zhang, Lei (Frontiers in Veterinary Science, 2022)
Citrobacter braakii is an opportunistic pathogen that induces aquatic infections in fish and turtles. In this study, a Myoviridae bacteriophage that infects C. braakii, named vB_CbrM_HP1, was isolated from sewage. We also used the phage to treat crucian carp infection caused by C. braakii for the first time. vB_CbrM_HP1 was relatively stable at temperatures ranging from 4 °C to 60 °C and pH values ranging from 3 to 11 but float slightly. When the multiplicities of infection (MOI) was 0.0001, the titre reached a maximum of 4.20×1010 PFU/mL. As revealed from the results of whole genomic sequence analysis, the total length of vB_CbrM_HP1 was 89335 bp, encoding 135 ORFs, 9 of which were less than 75% similar to the known sequences in NCBI. The phage vB_CbrM_HP1 showed a highly efficient bactericidal effect against C. braakii both in vitro and in vivo. In vitro, vB_CbrM_HP1 was capable of effectively killing bacteria (the colony count decreased by 4.7 log units at 5 h). In vivo, administration of vB_CbrM_HP1 (1×109 PFU) effectively protected crucian carp against fatal infection caused by C. braakii. Phage treatment reduced the levels of inflammatory factors. All these results demonstrated the potential of vB_CbrM_HP1 as an alternative treatment strategy for infections caused by C. braakii.